THE EVALUATION OF CIPP MODEL IN LEARNING CENTERS IN ISLAMIC KINDERGARTEN DARUSSALAM PALANGKARAYA - Siti Aviatur rosyiah; Saudah saudah; Rodhatul Jennah Jennah (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2022)
This study aims to describe the implementation of the evaluation using the CIPP model (Context, input, process, and product) in the learning center at Islamic Kindergarten Darussalam Palangka Raya. This research is a qualitative descriptive study. Using participatory observation methods, in-depth interviews, and documentation. While the data analysis technique uses data collection, data display, Conclusions Drawing verifying, data reduction. The results showed that the implementation of the evaluation of the CIPP model in learning centers at Islamic Kindergarten Darussalam Palangka Raya refers to the readiness of teachers, student capacities, and community considerations so that in the context of the institution chooses the type of learning center model to be applied. The goal is to support the educational strategy determined and developed by the institution. Evaluation of inputs: see the readiness of the institution in implementing the learning center program that has been designed and the availability of human resources, facilities and infrastructure as well as funds that can support the implementation of the program so that it is carried out in accordance with the objectives. Process evaluation: the readiness of the institution in designing the central learning program planning, measuring success and providing feedback for further program improvement. Evaluation of results: the decision-making stage of the central learning program that has been implemented for modification or continued in the next period.